Management of Social Risks and their Impact on the Spheres of Human Life in the Conditions of Sustainable Development of Ukraine - Zelinska, Halyna; Andrusiv, Uliana; Galtsova, Olga; Dmytrechenko, Mykyta (Problemy Ekorozwoju, 2021)
The aim of the article is to analyze risks in the social sphere and their impact on the development of society in Ukraine. Increasing the impact of risks in the sphere of demography, employment, remuneration, etc. in the context of sustainable development has been determined. The conducted research shows that the risks related to the labor sphere and the health of the population are the most aggressive and dangerous for the safety (as shown by the coronavirus pandemic) because protracted problems in the political, social and economic spheres are accompanied by job losses, economic decline, low wages for more than half of the working population. In view of the ambiguity and uneven economic development of the administrative territorial units of Ukraine it has been determined that education and knowledge can become a factor that can lead to the activation of innovative changes and reduce the negative impact of social threats. For this reason, the most important requirement for the sustainable development of Ukraine is the formulation of a social policy, based on an effective system of methods aimed at preventing risks and reducing probability of their occurrence.